IMPLEMENTAR A LA LEY ORGÁNICA DE SALUD COMO POLÍTICA DE ESTADO LA CREACIÓN DE INSTITUCIONES DE SALUD QUE PRESTEN LOS CUIDADOS PALIATIVOS EN FORMA GRATUITA PARA LOS PACIENTES ENFERMOS CON CANCER TERMINAL - Orellana Espinoza, Katherine Cecilia (2019)
This thesis entitled: ""IMPLEMENTING THE ORGANIC LAW AS STATE POLICY THE CREATION OF HEALTH INSTITUTIONS THAT PROVIDE PALLIATIVE CARE FREE FOR PATIENTS SICK WITH TERMINAL CÁNCER" refers to the presence of an illness in its terminal phase in one of the components of great impact on the patient and the family. When we talk about terminal patient, we must have very clear concepts. First, defining terminal disease, which is an incurable and progressive disease with limited possibilities of response to find a specific treatment, associated with the presence of multiple symptoms; They are of important emotional impact both in the patient and in the family. In this situation, in which it is impossible to raise the cure of the patient as a goal to achieve, our goal will focus on improving their quality of life through adequate symptom control and emotional support that both the patient and his family require. Secondly, taking into account what palliative care consists of is the comprehensive, individualized and continuous care of patients and their families. The needs identified must be met in a competent and timely manner, with the aim of alleviating suffering and improving the comfort and quality of life, of the sick and their families and according to their values, preferences and beliefs. Since every patient with terminal illness has the right to an integral assistance, which makes him/her a dignified death. Although most people with advanced oncological diseases probably most do not receive the care or treatment needed for this type of disease.